The Effectiveness of Cooperative Model And Problem Based Learning (Pbl) Assisted By Pop Up Books Media Toward Critical Thinking Skill of Elementary School Students - Endang Listiani, Yayuk; Tri Atmaja, Hamdan; Purwanti, Eko (Educational Management, 2019)
This study aimed to determine the effect and differences in the use of the cooperative model Think Talk Write and Problem Based Learning aided by Pop Up Books media on the critical thinking skills of elementary school students. This research used a quantitative research method of quasi experiment. The research design used in the study was the pretest-posttest control group design. The sample of this research was SD 1 Rahtawu and SD 2 Rahtawu as the control class and SD 1 Menawan as the experimental class. The control class consisted of 39 students and the experimental class consisted of 40 students. The independent variable was the cooperative model Think Talk Write and Problem Based Learning aided by Pop Up Books media. While the dependent variable was students' critical thinking. The data collection technique was a test of students' critical thinking results. With the results of the average value obtained by the control class 79.1, while in the experimental class the average value is 82.6. With an average N-gain in the experimental class is 0.51 in the medium category, while the average N-gain in the control class is 0.31 in the medium category. Which means there was an influence of the application of the cooperative model Think Talk Write and Problem Based Learning aided by Pop Up Books media on students' critical thinking skills. And there were differences in results in the use of learning models which means that by applying the Problem Based Learning model aided by Pop Up Books media students' critical thinking skills were better than the Cooperative Think Talk Write model aided by Pop Up Books media.